1987
DOI: 10.1007/bf00390867
|View full text |Cite
|
Sign up to set email alerts
|

Association of macrophages detected with monoclonal antibody 25 F 9 with progression and pathobiological classification of gastric carcinoma

Abstract: Using monoclonal antibody 25 F 9, which reacts with a determinant of mature macrophages, the inflammatory infiltrate of 66 gastric carcinomas was evaluated using a counting grid. The ratio tumor cells/macrophages was determined for every tumor. For a threshold value of 5, carcinomas with a better prognosis, such as the intestinal type according to Lauré, the expanding type according to Ming and the differentiated carcinomas according to the WHO had a significantly smaller relative content of 25 F 9-positive ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The prognostic significance of tumour-associated inflammatory cells is less clear in gastro-oesophageal cancer. An increased macrophage infiltrate was associated with more advanced stage of disease among patients with gastric cancer in one study, whereas other studies have suggested a more favourable prognosis associated with a more pronounced macrophage infiltration (Heidl et al, 1987;Tsujitani et al, 1987;Ohno et al, 2003). Similarly, increasing tumour-infiltrating lymphocyte count has been linked with decreased risk of death from gastric cancer in one study, but associated with an adverse prognosis in another (Setala et al, 1996;Grogg et al, 2003).…”
Section: Discussionmentioning
confidence: 80%
“…The prognostic significance of tumour-associated inflammatory cells is less clear in gastro-oesophageal cancer. An increased macrophage infiltrate was associated with more advanced stage of disease among patients with gastric cancer in one study, whereas other studies have suggested a more favourable prognosis associated with a more pronounced macrophage infiltration (Heidl et al, 1987;Tsujitani et al, 1987;Ohno et al, 2003). Similarly, increasing tumour-infiltrating lymphocyte count has been linked with decreased risk of death from gastric cancer in one study, but associated with an adverse prognosis in another (Setala et al, 1996;Grogg et al, 2003).…”
Section: Discussionmentioning
confidence: 80%
“…Macrophage accumulation in tumours is known to correlate with poor patient prognosis in the majority of cancer types (Fujimoto et al, 2000;Hamada et al, 2002;Hanada et al, 2000;Heidl et al, 1987;Leek et al, 1996;Lissbrant et al, 2000;Salvesen and Akslen, 1999). This can be explained by the tumour-promoting phenotype of TAMs, induced by the tumour microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation that is also seen between hypoxia and TAM numbers in secondary liver tumours that form as metastases from breast and colorectal tumours (Stessels et al, 2004). There is an inverse relationship between TAM infiltration and patient prognosis seen in many human cancers (Fujimoto et al, 2000;Hamada et al, 2002;Hanada et al, 2000;Heidl et al, 1987;Leek et al, 1996;Lissbrant et al, 2000;Salvesen and Akslen, 1999), which implies that these macrophages adopt a pro-tumoural phenotype, contrasting with their more classic role as pathogen and tumour killing cells and with their ability to initiate an immune response.…”
Section: Hypoxia and Its Impact On Macrophage Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors found that in malignant melanomas and gastric carcinomas 27E1O0 and 25F9+ macrophages were associated with tumour progression (Brocker et al, 1987;Heidl et al, 1987;Brocker et al, 1988). In acute gingival inflammation the dominant Mo/MO population carried the 27E10 antigen, whereas the numbers of Rm3/1 and 25F9 positive cells were low (Zwadlo et al, 1985(Zwadlo et al, , 1986.…”
Section: Discussionmentioning
confidence: 99%